Culturally sensitive psychotherapy—technique or attitude? - Stingl, Markus; Hanewald, Bernd (Frontiers in Psychology, 2025)
Culturally sensitive psychotherapy is essential in increasingly diverse societies, where cultural, religious, and linguistic differences shape how distress is experienced and communicated. This article conceptualizes culturally sensitive psychotherapy not only as a set of techniques, but as a reflective professional attitude. Drawing on models of intercultural competence and clinical examples, the article explores how culture affects the expression of symptoms, help-seeking behavior, and therapeutic relationships, especially among migrants. Integrating the cultural contexts enhances diagnostic accuracy, therapeutic alliance, and treatment outcomes. The approach balances awareness of cultural influence with the risk of stereotyping, urging clinicians to adopt a self-reflective stance. Culturally sensitive psychotherapy thus fosters effective and respectful care across diverse populations.